Reduction of the Appell's System of Partial Differential Equations to the System of Total Differential Equations (Journal of Partial Differential Equations, 2020)
In this paper it is shown that the Appell's system of partial differential equations, with two complex variables x and y, reduces to the system of total differential equations. Also, it is obtained the differential equation on the section y=const.